Galactomannan in Bronchoalveolar Lavage Fluid for Diagnosis of Invasive Pulmonary Aspergillosis with Nonneutropenic Patients - Qidong Zhuang; Hongying Ma; Yun Zhang; Lei Chen; Li Wang; Lin Zheng; Zaichun Deng; Zhongbo Chen (Canadian Respiratory Journal)
Background. We evaluated the utility of galactomannan (GM) in bronchoalveolar lavage fluid (BALF) for the diagnosis of invasive pulmonary aspergillosis (IPA) in nonneutropenic patients. Methods. A total of 183 patients were included in the final analysis. Bronchoscopies and the detection of GM in BALF were all performed on them. Results. Ten cases of IPA were diagnosed. ROC data demonstrated that, for diagnosing IPA, an optimal cutoff value for GM in BALF of 0.76 yielded a sensitivity of 100.0% and a specificity of 76.2%. Symptoms and radiological findings had no significant difference between proven or probable IPA group and non-IPA group. In our case-control analysis, although nine patients with false-positive results received treatment with Piperacillin/tazobactam, there was no significant difference between case and control group. Conclusions. BALF GM detection is a valuable adjunctive diagnostic tool. Our retrospective study suggests that the optimal value of GM detection in BALF is 0.76 in nonneutropenic patients.